Baseline Testosterone Predicts Body Composition and Metabolic Response to Testosterone Therapy - Deepika, FNU; Ballato, Elliot; Colleluori, Georgia; Aguirre, Lina; Chen, Rui; Qualls, Clifford; Villareal, Dennis T.; Armamento-Villareal, Reina (Frontiers in Endocrinology, 2022)
Context Male hypogonadism adversely affects body composition, bone mineral density (BMD), and metabolic health. A previous report showed that pre-treatment testosterone (T) levels of <200 ng/dl is associated with greater improvement in spine BMD with T therapy. However, to date, there is no study that investigates whether baseline T levels also influence body composition and metabolic response to T therapy. Objective The aim of this study is to determine if there are differences in the changes in body composition, metabolic profile, and bone turnover markers, in addition to BMD, in response to T therapy in men with a baseline T level of <264 ng/dl compared to those with levels ≥264 ng/dl. Methods This is a secondary analysis of a single-arm, open-label clinical trial (NCT01378299) on pharmacogenetics of response to T therapy conducted between 2011 and 2016 involving 105 men (40–74 years old), with average morning T < 300 ng/dl, given intramuscular T cypionate 200 mg every 2 weeks for 18 months. Subjects were divided into those with baseline T levels of <264 ng/dl (N = 43) and those with ≥264 ng/dl (N = 57). T and estradiol (E2) were measured by liquid chromatography/mass spectrometry; serum bone turnover markers (C-telopeptide [CTX], osteocalcin, and sclerostin), adiponectin, and leptin were measured by enzyme-linked immunosorbent assay; glycated hemoglobin (HbA1c) was measured by high-performance liquid chromatography; and areal BMD and body composition was measured by dual-energy x-ray absorptiometry (DXA). Results Men with T < 264 ng/dl showed greater increases in total fat-free mass (FFM) at 18 months compared to those with T ≥ 264 ng/dl (4.2 ± 4.1 vs. 2.7 ± 3.8%; p = 0.047) and unadjusted appendicular FFM at 6 and 18 months (8.7 ± 11.5 vs. 4.4 ± 4.3%, 7.3 ± 11.6 vs. 2.4 ± 6.8%; p = 0.033 and p = 0.043, respectively). Men with T ≥ 264 ng/dl showed significant decreases in HbA1c at 12 months (−3.1 ± 9.2 vs. 3.2 ± 13.9%; p = 0.005), fasting glucose at 18 months (−4.2 ± 31.9 vs. 13.0 ± 57.3%; p = 0.040), LDL at 6 months (−6.4 ± 27.5 vs. 12.8 ± 44.1%; p = 0.034), and leptin at 18 months (−40.2 ± 35.1 vs. −27.6 ± 31.0%; p = 0.034) compared to those with T < 264 ng/dl. No significant differences in BMD and bone turnover markers were observed. Conclusion T therapy results in improvement in body composition irrespective of baseline T levels but T < 264 ng/dl is associated with greater improvement in FFM, whereas a T level of ≥264 ng/dl favors improvement in metabolic profile.